Comparisons of Acuron, Surestart II, and Valor for Residual Weed Control in Grain Sorghum - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2019)
Herbicides were compared to standard treatments for preplant efficacy and crop response in grain sorghum. All herbicides controlled buffalobur and velvetleaf similarly late in the season. SureStart II and Acuron provided the best Palmer amaranth, puncturevine, and green foxtail control. Valor at 1 or 2 oz/a provided less than 70% puncturevine and green foxtail control late in the season. Only minimal visual injury was observed, and all herbicides increased sorghum yield 47–122% relative to the untreated controls.
Keywords: crop response